Sensitivity to Sea Ice Thickness Parameters in a Coupled Ice‐Ocean Data Assimilation System - Carmen Nab; Davi Mignac; Jack Landy; Matthew Martin; Julienne Stroeve; Michel Tsamados (Journal of Advances in Modeling Earth Systems)
Abstract Sea ice thickness (SIT) estimates derived from CryoSat‐2 radar freeboard measurements are assimilated into the Met Office's Forecast Ocean Assimilation Model. We test the sensitivity of winter simulations to the snow depth, radar freeboard product and assumed radar penetration through the snowpack in the freeboard‐to‐thickness conversion. We find that modifying the snow depth has the biggest impact on the modeled SIT, changing it by up to 0.88 m (48%), compared to 0.65 m (33%) when modifying the assumed radar penetration through the snowpack and 0.55 m (30%) when modifying the freeboard product. We find a doubling in the thermodynamic volume change over the winter season when assimilating SIT data, with the largest changes seen in the congelation ice growth. Next, we determine that the method used to calculate the observation uncertainties of the assimilated data products can change the mean daily model SIT by up to 36%. Compared to measurements collected at upward‐looking sonar moorings and during the Operation IceBridge campaign, we find an improvement in the SIT simulations' variability representation when assuming partial radar penetration through the snowpack and when improving the method used to calculate the CryoSat‐2 observation uncertainties. This paper highlights a concern for future SIT data assimilation and forecasting, with the chosen parameterization of the freeboard‐to‐thickness conversion having a substantial impact on model results.